Poland under German occupation, 1939-1945 : new perspectives - Huener, Jonathan, 1963- 1963- Herausgeber; Löw, Andrea, 1973- 1973- Herausgeber (Vermont studies on Nazi Germany and the Holocaust, 2024)
"As a unique and innovative addition to the scholarship on Nazi Germany, the Holocaust, and modern Polish history, this volume provides fresh analysis on the Nazi occupation of Poland. Through new questions and engaging untapped sources the leading historians who have contributed to this volume provide original scholarship to steer debates and expand the historiography surrounding Nazi racial and occupation policies, Polish and Jewish responses to them, persecution, police terror, resistance, and complicity"--